Reading Comprehension Skill By Using Cooperative Learning Type of Talking Stick - Khanifatul Fitriyah, L; Winarni, R; Murwaningsih, T (KnE Social Sciences, 2019)
Reading is one of four elements of language that is very important to be mastered by students. Skills of students in comprehension of a reading is very important that students have a broad insight. Therefore it is important to improve students’ motivation in reading, given that the reading motivation of students is still quite low seen from the results of PISA survey. This article discusses the talking stick type of cooperative learning that can help teachers in implementing the process of reading comprehension learning. One of the benefits of learning with cooperative type of talking stick is to train students to read and understand exactly. So that the talking stick type of cooperative learning is not only useful for speaking skills but also for reading skills. Reading is one of four important language skills that needs to be mastered by students. To be able to understand reading materials well, students must have broad insights. To have good insight of reading, ones must have a motivation to do it. The PISA survey shows that the Indonesian students’ reading was low. To improve the students’ motivation in reading, a talking stick was used. Talking stick is one example of cooperative learning strategies that can help teachers in implementing the process of reading comprehension learning. One of the benefits of talking stick is to train the students to read and understand well. Keywords: comprehension skill, cooperative learning, reading, talking stick.